Role of P-Glycoprotein Inhibitors in the Bioavailability Enhancement of Solid Dispersion of Darunavir. (31st October 2017) - Rehman, Saleha; Nabi, Bushra; Fazil, Mohammad; Khan, Saba; Bari, Naimat Kalim; Singh, Romi; Ahmad, Shavej; Kumar, Varinder; Baboota, Sanjula; Ali, Javed
Abstract : Objective. The aim of the present study was to improve bioavailability of an important antiretroviral drug, Darunavir (DRV), which has low water solubility and poor intestinal absorption through solid dispersion (SD) approach incorporating polymer with P-glycoprotein inhibitory potential. Methods. A statistical approach where design of experiment (DoE) was used to prepare SD of DRV with incorporation of P-glycoprotein inhibitors. Using DoE, different methods of preparation, like melt, solvent evaporation, and spray drying method, utilizing carriers like Kolliphor TPGS and Soluplus were evaluated. The optimized SD was characterized by DSC, FTIR, XRD, and SEM and further evaluated for enhancement in absorption using everted gut sac model, effect of food on absorption of DRV, and in vivo prospect. Results and Discussion. DSC, FTIR, XRD, and SEM confirmed the amorphicity of drug in SD. Oral bioavailability studies revealed better absorption of DRV when given with food. Absorption studies and in vivo study findings demonstrated great potential of Kolliphor TPGS as P-glycoprotein inhibitor for increasing intestinal absorption and thus bioavailability of DRV. Conclusion. It is concluded that SD of DRV with the incorporation of Kolliphor TPGS was potential and promising approach in increasing bioavailability of DRV as well as minimizing its extrusion via P-glycoprotein efflux transporters.